General surgery principles and international practice - Bland, Kirby I. (Springer London, 2009)
General Surgery: Principles and International Practice is organized into Ten Sections, each representing an important branch of surgical science. It aims to provide the medical student, general surgical resident or active practitioner with an illustrative, instructive and comprehensive textbook depicting the rationale for the basic operative principles mandated by state-of-the-art surgical therapy. The reader can rapidly review the subject matter in a three-to-five page summary with contemporary bibliography in each chapter and a “Pearls and Pitfalls” section summarizing the ‘impact’, concerns and outcomes of surgical management. Amply supported by line drawings and photographs, algorithms and anatomical depictions, this provides the student of diseases, as well as those studying for Board examinations, a text that has rapidly assimilated data into the most contemporary applications of surgical therapy.